Study on Recurrent Anterior Shoulder Dislocation: An Approach to Boytchev Treatment - Benabdallah, Otman; Khamlichi, Ahmed (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
Background: The Boytchev method, which has been used since 1951 to treat anterior glenohumeral instability, is an open anterior repair that entails rerouting the muscles that join the coracoid process deep to the subscapularis muscle between this and the capsule. In the anatomical position, the tip of the coracoid is reattached to its base by its muscles. Methods: We conducted a prospective study of twenty patients with recurrent shoulder dislocations who were treated by the Boytchev procedure. All are men, with an average age of 29.2 years (age range from 17 to 42 years). 14 patients were affected on the right shoulder, 6 on the left. All had a clinical history of recurrent dislocation. We also performed a search of all published articles in the literature (16),17 studies including our series, with the aim of estimating, via a statistical analysis, to shed light on the post-operative results of recurrent anterior dislocations of the shoulder, for determining the reliability of this technique and possible specific risk factors that might lead to recurrence. Results: Evaluated using the Rowe score in our series, 19 patients had excellent and good results; one patient, who suffered a recurrence, had a poor result in terms of stability. Another patient developed osteoarthrosis. For the 17 studies, the number of patients is 477 with 485 dislocated shoulders. The rate of recurrence is 7.33% .In 12 studies, the rate is 2%, versus 21.05% in 5 studies with a significant difference (1-p=99.89%). Concerning the gradation of results, we have 441 excellent and good results and 44 fair and poor (91% versus 9% with p=>99.9% which is also very significant). Conclusion: The Boytchev procedure exhibits low recurrence rates in compiled studies and so can be considered a reliable surgical technique.